Welcome to Westonci.ca, your go-to destination for finding answers to all your questions. Join our expert community today! Get immediate and reliable answers to your questions from a community of experienced professionals on our platform. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

(6a⁴)³
reduse the equation to its simplest form​


Sagot :

Answer:

Step-by-step explanation:

Two properties used are: [tex](a*b)^{m} = a^{m}*b^{m}\\[/tex]  and  [tex](a^{m})^{n}=a^{m*n}[/tex]

[tex](6a^{4})^{3}=6^{3}*(a^{4})^{3} = 216a^{4*3} = 216a^{12}[/tex]